MEDIA POP CULTURE IN THE PROCESS OF SHAPING THE IDENTITY OF YOUTH - Piechaczek-Ogierman, Gabriela (Educological discourse, 2018)
Media pop culture does not only shape the world view but also creates trends and is a source of inspiration and identification of the young. The research results presented in this study show that youth in the final stage of adolescence judge the reality in a critical way. A significant number of the examined learners implement the model of identity shaped in the «down top» direction. They reject media authorities and aim at creating their own concept of themselves. At the same time, a large percentage of the respondents respect media models associated with appearance and the consumerist lifestyle.